The contribution of a history of heavy smoking to Scotland's mortality disadvantage. (2nd January 2016) - Kelly, Laura A.; Preston, Samuel H.
Abstract : Scotland has a lower life expectancy than any country in Western Europe or North America, and this disadvantage is concentrated above age 50. According to the Human Mortality Database, life expectancy at age 50 has been lower in Scotland than in any other developed country since 1980. Relative to 15 developed countries that we have chosen for comparison, Scotland's life expectancy in 2009 at age 50 was lower by an average of 2.5 years for women and 1.6 years for men. We estimate that Scottish women lost 3.6 years of life expectancy at age 50 as a result of smoking, compared to 1.4 years for the comparison countries. The equivalent figures among men are 3.1 and 2.1 years. These differences are large enough for the history of heavy smoking in Scotland to account both for most of the shortfall in life expectancy for both sexes and for the country's unusually narrow sex differences in life expectancy.